Analysis of the Availability of Mosque Sanitation Facilities in the Tsunami Green Area as an Alternative Place for The Final Evacuation of the Tsunami Disaster in Padang City - Mahaza Mahaza; Erdi Nur; Awalia Gusti; Sari Arlinda; Murniati Murniati; Riyana Husna (Universitas Aisyah Pringsewu, 2023)
The city of Padang as one of the areas in West Sumatra which is in a coastal area is very prone to tectonic earthquakes with the potential for tsunamis, it is verynecessary to have high preparedness to deal with it. One of the things that must be prepared is the evacuation site the end, which is a temporary residence for disaster victims. One alternative that can be used as a final evacuation site is a mosque. This study aims to prepare mosque sanitation facilities in the tsunami green area. The measurement of the preparedness of mosque sanitation facilities is seen from observations, in the form of a checklist table that will be filled out by researchers in 29 mosques that are the object of study. With a descriptive type of research, to see an overview of the condition of mosque sanitation facilities. Based on the results of research and discussion, it can be concluded that from the 29 mosques studied, all mosques were obtained in the category of sanitation, construction, toilets and latrines, lighting and ventilation conditions of mosques in the city of Padang. While 17 mosques (58.6%) are located close to Jalan Raya, there are 25 mosques (86.2%) with courtyards in good condition, there are 28 mosques (96.6%) with good waste management, 13 mosques (44.8%) using water sources from PDAM and there are 28 mosques (96.6%) that have wastewater disposal in good condition. This can be used as an evacuation site, so the main thing that must be done is the maintenance of the sanitary condition of the mosque so that it is maintained and can become a proper evacuation site.